Bacterial Communities Associated with Crude Oil Bioremediation through Composting Approaches with Indigenous Bacterial Isolate - Nilita Mukjang; Thararat Chitov; Wuttichai Mhuantong; Verawat Champreda; Wasu Pathom-aree; Pachara Sattayawat; Sakunnee Bovonsombut (Life, 2022)
In this study, we aim to investigate the efficiency of crude oil bioremediation through composting and culture-assisted composting. First, forty-eight bacteria were isolated from a crude oil-contaminated soil, and the isolate with the highest crude oil degradation activity, identified as Pseudomonas aeruginosa, was selected. The bioremediation was then investigated and compared between crude oil-contaminated soil (S), the contaminated soil composted with fruit-based waste (SW), and the contaminated soil composted with the same waste with the addition of the selected bacterium (SWB). Both compost-based methods showed high efficiencies of crude oil bioremediation (78.1% and 83.84% for SW and SWB, respectively). However, only a slight difference between the treatments without and with the addition of P. aeruginosa was observed. To make a clear understanding of this point, bacterial communities throughout the 4-week bioremediation period were analyzed. It was found that the community dynamics between both composted treatments were similar, which corresponds with their similar bioremediation efficiencies. Interestingly, Pseudomonas disappeared from the system after one week, which suggests that this genus was not the key degrader or only involved in the early stage of the process. Altogether, our results elaborate that fruit-based composting is an effective approach for crude oil bioremediation.